Effectiveness of Humic Acid Application on Growth of Coffee Seedings - Niken Puspita Sari; Soetanto Abdoellah (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Soil fertility is an important aspect to consider in a plantation because it can affect plantation productivity. Furthermore, degradation of soil fertility issue is increasing therefore it needs innovation to improve soil fertility. Humic acid is an alternative material which can be used for improving soil fertility and supporting plantation production. This research objective was to investigate the effectivenes of humic acid for growth of coffee seedlings. This research was done in Indonesian Coffee and Cocoa Research Institute green house. Experi-ment used completely randomized design trial with two factors. First factor was the materials used humic acid, coffee pulp compost, and manure. Second factor was doses of materials: 0 g, 10 g, and 30 g per 2 kg dry soil. Research parameters used plant height, number of leaves, stem diameter, wet weight, soil carbon, N, Pavailable, K available, and pH analysis. The results showed that humic acid 30 g significant increasing plant height and K available. Furthermore, humic acid dose 10 g and 30 g resulted root, stem diameter, and leaves weight were better than compost from coffee pulp and manure. Soil carbon was increase after humic acid, compost from coffee pulp, and manure application. Humic acid, compost from coffee pulp, and manure made soil pH were stabile.